SISTEMA MÓVIL PARA LA REDUCCIÓN DE DESECHOS FLOTANTES DEL RÍO BABAHOYO - ROSADO ESCOBAR, MARJORIE VANESSA (2019)
The generation of floating debris is inescapable, unfortunately all of them cause negative impacts on the environment, water pollution is mostly caused by plastics that have ended the lives of many species by drowning, especially with turtles, whose bags have colonized all the seas that in the not too distant future the so-called floating continent will be formed. Pollution of waters, whether in rivers, seas, streams, has been generated for many years due to the different activities carried out by human beings, one of which is produced by the waste that is thrown into the rivers, reducing the animal life, encouraging the proliferation of diseases. Today the advance of technology has allowed society to benefit greatly, with the development of telecommunications systems, which interconnected with other technologies would achieve collection systems that benefit the environment. On the other hand, different ecosystems are affected by these wastes that are thrown into the river, having a system that is used to collect the waste in the river and not accelerate the polluting percentage in our planet. The present system was developed using the sub-line of Development of Computer Systems, using as a technique observation and as an instrument the interview, which provided important information about the problems that contribute negatively to society, for its proper development.